Villous adenoma of the urinary bladder: rare location - Atik, Esin; Akansu, Bülent; Davarci, Mürsel; Inci, Mehmet; Yalcinkaya, Fatih; Rifaioglu, Murat (Contemporary Oncology/Współczesna Onkologia, 2012)
Villous adenomas are common lesions of the gastrointestinal tract but they are rarely located in the urinary tract including the urinary bladder. There are a few case reports and series in the literature. Here we report a 43-year-old male patient who had a polypoid lesion located on the left lateral wall of the urinary bladder. Transurethral resection was performed. The diagnosis was ‘villous adenoma of urinary bladder’ with clinical and histopathological findings. Villous adenomas are mostly seen in elderly males. The coexistence of villous adenoma with adenocarcinoma, squamous cell carcinoma, and urothelial carcinoma was observed but there is not clear evidence about progression to carcinoma, in spite of its colonic counterpart. Generally complete surgical resection is accepted as curative but there are no exact data about follow-up and recurrence. By presenting this case, we aim to emphasize that it is a rare but important lesion because of coexistence with malignancies and uncertain malignant potential.